Introducing system interdependency into infrastructure appraisal: from projects to portfolios to pathways - Young, K; Hall, J (Springer, 2015)
Current methods for appraisal of infrastructure projects have been developed to consider multiple criteria, wider economic impacts and uncertainty, yet their focus on standalone projects and sector specific methods ignores the widely acknowledged ‘system of system’ interactions between infrastructure networks. Here we draw inspiration from real options ‘in’ projects to build on current appraisal methods, extending the analysis from single projects to cross-sector regional portfolios and finally to temporally differentiated development pathways; quantifying each stage through a case study on the Thames Hub Vision. The result is a system perspective of the investments, including: (i) the emergent effects of infrastructure asset interactions and how these are affected by the timing and order of development; (ii) an understanding of the ‘opportunity’ value of an investment through its ability to restrict or enable further developments; and (iii) the total required resources and potential environmental outcomes. Through our case study we demonstrate these effects, identifying system effects sufficient to reverse the outcome of the analysis from a net negative, to a net positive result. Furthermore, we show that the enabling effects of an asset on future developments can create impacts an order of magnitude larger than those observed through current individual asset appraisals. Our developments allow the creation of a decision support tool capable of more fully evaluating the effects of infrastructure investments, with a focus on the long-term opportunity provided by development strategies. The work provides a platform for prioritisation of investments across sectors and for highlighting cross-sector effects, thereby encouraging stakeholder engagement and collaboration. Further work is necessary to explore the effects of intrinsic socio-economic uncertainty in the modelling assumptions and feedbacks between investments and future projections, such as population change and economic growth.